Irony's edge : the theory and politics of irony - Hutcheon, Linda, 1947- (Routledge, 1995)
There is the growing sense that irony has emerged as a mode of expression that is strangely out of vogue. The popular press has veritably written it off as a means of critique. Politicians and pundits seldom use it. And when they do, it tends either to miss its intended mark or, for that matter, induce widespread cognitive failure. Yet, irony is a complex rhetorical move. It depends on deep and shared levels of understanding, knowing namely, that one means what one doesn't mean and that that actually means something else completely. It produces a "scene." In Irony's edge, Linda Hutcheon examines the nature of this "scene." She explores what constitutes irony, how irony functions, in what ways it is political, and how it disrupts the space between expression and understanding. She examines irony not only as an intercommunicative act, but as a discursive practice that is, in many ways, a cultural event, which happens in discrete and often sophisticated ways. She analyzes irony's logic and the way in which it operates in relations to concepts of difference and identity, intentionality and interpretation, and the inappropriate and the appropriate. She examines these concerns vis-a-vis an array of references gathered from contemporary and modern culture. She looks at works such as the novels of Umberto Eco, the operas and symphonies of Richard Wagner, and the art of Anselm Kiefer. She focuses on popular cultural figures such as Madonna and the recent film of Shakespeare's Henry V. Her book is one of the first synthesized theoretical accounts of the cultural phenomenology of irony. In Irony's edge, Hutcheon elaborates upon her earlier work on parody (A theory of parody) and scrutinizes the mechanics of irony in fundamentally salient and critical ways